P030 Intravital observation system of the colon by two photon excitation microscopy. (16th January 2018) - Fukuhara, T; Ueda, Y; Kamioka, Y; Okazaki, K; Kinashi, T
Abstract: Background: Cell dynamics throughout the body is an essential event for immune cells to work properly against pathogens or other targets. When intestines are inflamed, many immune cells including lymphocytes migrate from blood vessels to lamina propria. On this process, immune cells adhere to endothelium, change the morphology and migrate to interstitial tissue. Cell adherence and shape change is controlled by a group of adhesion molecules, integrins and their ligands. Recently, many anti-adhesion molecule antibodies are on market or under development for therapeutic use of inflammatory bowel disease. To investigate this immunological event, we have developed intravital observation system using two photon excitation microscopy. Methods: Fluorescent YFP or EGFP transgenic mouse is anaesthetised and a small incision is made at the lower abdomen. A part of large intestine is pulled out and clipped. The organ is filled with soft agar and attached to the custom-built suction device to immobile. Blood vessel is coloured by intravenous administrating of Evansblue. The wave length of two photon excitation laser is set to 840 nm. Colitis is induced by oral administration of 1.5 to 3.0% dextran sulfate sodium for seven days. Mice for this study are treated under the guideline for proper use of experimental animals of the institute. Results: Immune cell movement in small vessels and in lamina propria can be observed in the colon of living mouse. The maximum observation time was 5 h. The change of cell shape was also seen clearly. Under the inflamed condition, more immune cells are recruited to the region. Conclusions: Intravital observation system of the colon by two photon excitation microscopy is a powerful tool to study immune cell dynamics in physiological condition. Real-time cell movement in intestines of living mouse can be observed and analysed. This system could be applied to evaluate the effect of therapeutic reagent candidates for inflammatory bowel disease including adhesion inhibitory reagents, e.g. anti-α4 β7 integrin antibody.